Surface display of a borrelial lipoprotein on meningococcal outer membrane vesicles. Issue 8 (17th February 2016) - Salverda, Merijn L.M.; Meinderts, Sanne M.; Hamstra, Hendrik-Jan; Wagemakers, Alex; Hovius, Joppe W.R.; van der Ark, Arno; Stork, Michiel; van der Ley, Peter
Highlights: Borrelial lipoprotein OspA loses its outer-surface localization in Neisseria . Surface-display rescued by fusion to part of meningococcal surface-lipoprotein fHbp. OMVs with surface-exposed OspA elicit OspA-specific antibody responses in mice. New method for surface display of heterologous lipoproteins in OMVs. Abstract: Outer Membrane Vesicles (OMVs) are gaining attention as vaccine candidates. The successful expression of heterologous antigens in OMVs, with the OMV functioning both as adjuvant and delivery vehicle, has greatly enhanced their vaccine potential. Since there are indications that surface exposed antigens might induce a superior immune response, targeting of heterologous antigens to the OMV surface is of special interest. Several systems for surface display of heterologous antigens on OMVs have been developed. However, these systems have not been used to display lipidated membrane-associated proteins known as lipoproteins, which are emerging as key targets for protective immunity. We were therefore interested to see whether we could express a foreign lipoprotein on the outer surface of OMVs. When outer surface protein A (OspA), a borrelial surface-exposed lipoprotein, was expressed in meningococci, it was found that although OspA was present in OMVs, it was no longer surface-exposed. Therefore, a set of fusions of OspA to different regions of factor H binding protein (fHbp), a meningococcal surface-exposed lipoprotein, were designed and tested for their surface-exposure. An N-terminal part of fHbp was found to be necessary for the successful surface display of OspA on meningococcal OMVs. When mice were immunized with this set of OMVs, an OspA-specific antibody response was only elicited by OMVs with clearly surface-exposed OspA, strengthening the idea that the exact positioning of an antigen in the OMV affects the immune response. This method for the surface display of heterologous lipoproteins on OMVs is a step forward in the development of OMVs as a vaccine platform.